In vivo redukce radiocesia modifikovaným klinoptilolitem u ovcí - Jandl, J; Novosad, J (Veterinarni medicina, 1995)
The efficiency of the sorbent prepared by immobilization of [Iron(II)hexacyanoferrate(II)] on clinoptilolite--marked as ZEOFe--in reduction of the radiocaesium Cs-137 has been in vivo investigated in sheep. It was found that an application of this modified clinoptilolite affected both primary and secondary resorption of Cs-137 also by interrupting the enteral cycle of radiocaesium in sheep. It was proved that ZEOFe accelerated approx. twice the excretion of Cs-137 from sheep's body. The whole effect resulted in 15 to 50 times lowering of the equilibrium concentration of radiocaesium in the case of constant intake of the contaminated feed and simultaneous application of 50 grams of ZEOFe daily. The actual reduction depends mainly on the way of administration. The reduction of Cs-137 by non-modified clinoptilolite--ZEO--has been investigated, too. More than 10x lower sorption efficiency has been observed in comparison with ZEOFe.
Keywords: Cesium Radioisotopes; radioizotopy cesia; zeolity; Sheep; Animals; Zeolites; zvířata; ovce